2016
DOI: 10.1155/2016/2768365
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Related Diseases in Newborns

Abstract: We review oxidative stress-related newborn disease and the mechanism of oxidative damage. In addition, we outline diagnostic and therapeutic strategies and future directions. Many reports have defined oxidative stress as an imbalance between an enhanced reactive oxygen/nitrogen species and the lack of protective ability of antioxidants. From that point of view, free radical-induced damage caused by oxidative stress seems to be a probable contributing factor to the pathogenesis of many newborn diseases, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 93 publications
4
122
0
6
Order By: Relevance
“…However, it is now generally acknowledged that multiple additive or synergistic factors concur to the etiology of BPD and to the severity of the disease with the occurrence of pre-and postnatal causes. Although the strongest cause still remains preterm delivery, other aspects such as fetal infection and inflammation, mechanical ventilation, oxygen toxicity, impaired infant antioxidant activity, heart diseases, surfactant dysfunctions, patent ductus arteriosus, and postnatal infection all concur to the onset of BPD ( Figure 1) [38]. Indeed, airway inflammation is a key component of chronic lung diseases, such as cystic fibrosis, BPD, and asthma [39].…”
Section: Osmentioning
confidence: 99%
“…However, it is now generally acknowledged that multiple additive or synergistic factors concur to the etiology of BPD and to the severity of the disease with the occurrence of pre-and postnatal causes. Although the strongest cause still remains preterm delivery, other aspects such as fetal infection and inflammation, mechanical ventilation, oxygen toxicity, impaired infant antioxidant activity, heart diseases, surfactant dysfunctions, patent ductus arteriosus, and postnatal infection all concur to the onset of BPD ( Figure 1) [38]. Indeed, airway inflammation is a key component of chronic lung diseases, such as cystic fibrosis, BPD, and asthma [39].…”
Section: Osmentioning
confidence: 99%
“…[3][4][5][6][7] Oxidative stress has also been associated with increased risks for serious prematurity-associated morbidities, including necrotizing enterocolitis (NEC), late-onset sepsis, bronchopulmonary dysplasia (BPD), and neurodevelopmental problems. 8,9 Thus, a priority in improving outcomes in premature infants is to identify practices that prevent and/or mitigate oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research in several centres demonstrated the effect of these processes on embryonic and foetal development. Their effect on organogenesis cannot be excluded [1,2].…”
Section: Introductionmentioning
confidence: 99%